The implications of the European Union's new fiscal rules - Zsolt M. Darvas; Lennard Welslau; Jeromin Zettelmeyer (Bruegel, 2024)
European Union countries are required by the EU Treaty to keep their budget deficits within 3 percent of GDP, and their public debt within 60 percent of GDP. A new framework to enforce these rules is based on country-specific debt sustainability analyses (DSA) and uses a single indicator, a measure of public expenditure, as the annual fiscal policy target. These changes are welcome. To assess the sustainability of public finances, it is much better to focus on the likely evolution of the debt path than to rely on simple numerical rules. Public ex- penditures net of changes to tax policy are a far better target for fiscal policy than the deficit, since they are under the control of the government and cannot give rise to pro-cyclical fiscal policy (excess spending in good times, fiscal cuts in bad times). These features could increase the framework's efficiency and improve compliance. However, the new framework also contains numerical safeguards to ensure a minimum pace of debt and deficit reduction. These might overwrite the DSA-based requirements and could undermine the rationale for the new rules and the incentives for compliance. The safeguards could also introduce some pro-cyclicality and, more importantly, could hold back increases in public investment. Our calculations show that the new framework will require ambitious fiscal adjustments from high-debt countries, though less than would have been required by the previous frame- work. Numerical safeguards will not be a significant constraint in the first application of the framework in 2024, except for Finland. In the next application, in 2028, they imply for France and Italy greater fiscal adjustment than required by the DSA and the 3 percent benchmark. There is ambiguity about the consistency of the new fiscal rules and the largely-unchanged excessive deficit procedure (EDP), and whether proposed reforms and investment will influence the DSA. This could interfere with the successful application of the framework. We recommend that the EDP should require the same adjustment as the DSA, a method- ology should be developed to estimate the quantitative impact of proposed investments and reforms, and the DSA methodology should be revised. In case EU countries' investment plans on aggregate do not fill the green public-investment gap, we recommend a new EU facility to foster such investments.
Keywords: 330; European semester and fiscal rules; european commission; financial regulation; fiscal policy; eu governance; eu budget